PENGARUH MANAJEMEN KURIKULUM TERHADAP KREATIVITAS DAN KEMANDIRIAN PESERTA DIDIK DI SD DARUSSALAM - Setio Utomo; Muhamad Imam Khaudli (CV. Adiba Aisha Amira, 2025)
This study aims to analyze the influence of curriculum management on the creativity and independence of students at SD Darussalam Blokagung. The background of this study is based on the needs of today's education which is not only oriented towards academic achievement, but also on the development of character and potential of students as a whole. This study uses a qualitative approach with a case study type, which focuses on the practice of curriculum management in an elementary school environment based on Islamic boarding schools. Data collection techniques were carried out through in-depth interviews with the principal, teachers, and students, participatory observation of learning activities and religious habits, and documentation studies of curriculum documents and daily school activities. Data analysis was carried out using the Miles and Huberman interactive model, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that flexible and contextual curriculum management has proven effective in increasing student creativity through project-based learning activities, discussions, and direct practice. Meanwhile, the application of a contextual curriculum that is linked to everyday life encourages student learning independence. Teachers play an important role in shaping students' behavior and character through role models and the integration of values ​​in the learning process. This study recommends the need for adaptive curriculum management to build creative and independent students.